The right timing matters: Sensitive periods in the formation of socio-emotional skills - Laura Breitkopf; Shyamal K. Chowdhury; Daniel A. Kamhöfer; Hannah Schildberg-Hörisch; Matthias Sutter (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2025)
Identifying sensitive periods in which the returns to investments into skills are especially high is challenging, but crucial for an effective and efficient timing of parental or public investments aimed at fostering children's skills. We can detect sensitive periods with a novel design by implementing the same investment in different school grades and examining grade-specific treatment effects. Based on a randomized controlled trial with more than 3,200 Bangladeshi children in grades 2 to 5, we find sensitive periods in the formation of self-control and patience in grade 2 (age 7-8), while prosociality remains similarly malleable throughout grades 2 to 5 (age 7-11).
Keywords: C93; D01; D64; J13; 330; Sensitive periods; skill formation; randomized controlled trial; self-control; patience; prosociality; social and emotional learning program; experiments with children; Bangladesh